Performance management in the prosocial market economy: a new paradigm for economic performance and sustainability - Pfister, Jan A.; Otley, David; Ahrens, Thomas; Dambrin, Claire; Darwin, Solomon; Granlund, Markus; Jack, Sarah L.; Lassila, Erkki M.; Millo, Yuval; Peda, Peeter; Sherman, Zachary; Wilson, David Sloan (Emerald, 2025)
Purpose
The purpose of this multi-voiced paper is to propose a prosocial paradigm for the field of performance management and management control systems. This new paradigm suggests cultivating prosocial behaviour and prosocial groups in organizations to simultaneously achieve the objectives of economic performance and sustainability.
Design/methodology/approach
The authors share a common concern about the future of humanity and nature. They challenge the influential assumption of economic man from neoclassical economic theory and build on evolutionary science and the core design principles of prosocial groups to develop a prosocial paradigm.
Findings
Findings are based on the premise of the prosocial paradigm that self-interested behaviour may outperform prosocial behaviour within a group but that prosocial groups outperform groups dominated by self-interest. The authors explore various dimensions of performance management from the prosocial perspective in the private and public sectors.
Research limitations/implications
The authors call for theoretical, conceptual and empirical research that explores the prosocial paradigm. They invite any approach, including positivist, interpretive and critical research, as well as those using qualitative, quantitative and interventionist methods.
Practical implications
This paper offers implications from the prosocial paradigm for practitioners, particularly for executives and managers, policymakers and educators.
Originality/value
Adoption of the prosocial paradigm in research and practice shapes what the authors call the prosocial market economy. This is an aspired cultural evolution that functions with market competition yet systematically strengthens prosociality as a cultural norm in organizations, markets and society at large.